Methods of testing and assessing the technical condition of chosen building structures located in the area of the Auschwitz-Birkenau State Museum in Oświęcim = Metody badania i oceny stanu technicznego wybranych obiektów kubaturowych znajdujących się na terenie Państwowego Muzeum Auschwitz-Birkenau w Oświęcimiu - Kańka, Stanisław; Stryszewska, Teresa; Tracz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results presented in this article consider the means of assessing the technical condition of two selected buildings, i.e. prisoner barracks number 123 and 124, located at the Auschwitz-Birkenau State Museum in Oświęcim.
Keywords: Państwowe Muzeum Auschwitz-Birkenau; barak więźniarski; stan techniczny; wzmocnienia konstrukcji; technical condition; prisoner barracks; Auschwitz-Birkenau Concentration Camp